1993
DOI: 10.1101/gad.7.6.1097
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of a conditional GATA-2/estrogen receptor chimera arrests erythroid differentiation in a hormone-dependent manner.

Abstract: The GATA factors are a family of transcriptional regulatory proteins in eukaryotes that share extensive homology in their DNA-binding domains. One enigmatic aspect of GATA factor expression is that several GATA proteins, which ostensibly share the same DNA-binding site specificity, are coexpressed in erythroid cells. To elucidate the roles of individual GATA factors in erythropoiesis, conditional alleles of GATA-I, GATA-2, and GATA-3 were prepared by fusing each of the factors to the hormone-binding domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
1
5

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(161 citation statements)
references
References 43 publications
9
146
1
5
Order By: Relevance
“…GATA-2, originally cloned from a chicken cDNA library (1), was shown to be essential for the proliferation and/or differentiation of early hematopoietic progenitors, as Gata2 null mutant mice die around mid-gestation from a block in primitive hematopoiesis (2). Further examination of Gata2 gain-of-function mice and in vitro differentiation of Gata2 null mutant ES cells underscored the fundamental conclusions from the initial loss of function experiments, and showed that GATA-2 plays a pivotal role in the proliferation of very early hematopoietic progenitors (3)(4)(5).…”
mentioning
confidence: 93%
“…GATA-2, originally cloned from a chicken cDNA library (1), was shown to be essential for the proliferation and/or differentiation of early hematopoietic progenitors, as Gata2 null mutant mice die around mid-gestation from a block in primitive hematopoiesis (2). Further examination of Gata2 gain-of-function mice and in vitro differentiation of Gata2 null mutant ES cells underscored the fundamental conclusions from the initial loss of function experiments, and showed that GATA-2 plays a pivotal role in the proliferation of very early hematopoietic progenitors (3)(4)(5).…”
mentioning
confidence: 93%
“…SCF and TGFa dependent erythroid progenitor cells (referred to as SCF and TGFa progenitors, respectively) were prepared from bone marrow of 3 ± 10-day old SPAFAS chicks essentially as described (Hayman et al, 1993;Briegel et al, 1996;Wessely et al, 1997). Brie¯y, following Ficoll-Hypaque centrifugation (density 1.077 g/cm 3 , Eurobio, Paris, France) bone marrow cells were cultured in modi®ed CFU-E medium (2 ± 4610 6 cells/ml; Radke et al, 1982;Zenke et al, 1988;Beug et al, 1995) containing 100 ng/ ml avian SCF (Hayman et al, 1993;Bartunek et al, 1996).…”
Section: Cells and Tissue Culturementioning
confidence: 99%
“…After two days cell proliferation was determined by CellTiter 96 TM cell proliferation assay (Promega, Madison, WI, USA). Hemoglobin content of erythroid cells was measured as described (Briegel et al, 1993). All measurements were done in triplicate.…”
Section: Cell Proliferation and Hemoglobin Measurementsmentioning
confidence: 99%
See 2 more Smart Citations